1996
DOI: 10.1093/oxfordjournals.annonc.a010473
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of paclitaxel in patients with relapsed or cisplatin-refractory testicular cancer

Abstract: Paclitaxel demonstrates significant antitumor activity in 25% of patients with relapsed or cisplatin-refractory testicular cancer. Combination regimens including paclitaxel may be warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0
1

Year Published

1998
1998
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(61 citation statements)
references
References 7 publications
2
58
0
1
Order By: Relevance
“…20 The remaining seven patients, as well as patients with recurrence of disease after salvage high-dose chemotherapy, received further palliative treatment for refractory disease with various agents such as orally administered etoposide, oxaliplatin, bendamustine, or gemcitabine within trials of the GTCSG. [21][22][23][24] The tissue samples from patients with resistant disease were derived from tumors resected at initial diagnosis (n ϭ 14), from secondary resection of residual masses containing viable tumor cells (n ϭ 4), or from metastatic tumors (n ϭ 4). The specimens of the responsive cases were derived from orchiectomy (n ϭ 10) or from retroperitoneal biopsies (n ϭ 2).…”
Section: Patients and Tissue Samplesmentioning
confidence: 99%
“…20 The remaining seven patients, as well as patients with recurrence of disease after salvage high-dose chemotherapy, received further palliative treatment for refractory disease with various agents such as orally administered etoposide, oxaliplatin, bendamustine, or gemcitabine within trials of the GTCSG. [21][22][23][24] The tissue samples from patients with resistant disease were derived from tumors resected at initial diagnosis (n ϭ 14), from secondary resection of residual masses containing viable tumor cells (n ϭ 4), or from metastatic tumors (n ϭ 4). The specimens of the responsive cases were derived from orchiectomy (n ϭ 10) or from retroperitoneal biopsies (n ϭ 2).…”
Section: Patients and Tissue Samplesmentioning
confidence: 99%
“…In another phase II German trial, 24 patients with relapsed, mostly cisplatin-refractory, metastatic GCTs were treated with 3-hour paclitaxel infusions of 225 mg/m 2 every 3 weeks [15]. The patients had received a median of seven platinum-containing treatment cycles prior to paclitaxel, and 12 patients had previously received high-dose carboplatin/etoposide-based salvage therapy with autologous stem cell support.…”
Section: Paclitaxelmentioning
confidence: 99%
“…[56][57][58][59][60][61][62][63][64][65][66][67][68][69] Paclitaxel was shown to Chemo., chemotherapy; CR, complete response; NED, no evidence of disease; VeIP, vinblastine, ifosfamide, cisplatin; VIP, etoposide (VP-16), ifosfamide, cisplatin. be effective for previously treated testicular cancer because of its unique mechanism of antitumor activity and the premature stabilization of the microtubules assembly, which is different from that of DNAdamaging agents such as cisplatin and ifosfamide.…”
Section: Poor-prognosis Diseasementioning
confidence: 99%
“…The first trial of paclitaxel in pretreated germ cell tumors was undertaken by Motzer et al 56 The effective rate of paclitaxel in the salvage treatment of refractory testicular cancer ranged from 11 to 26% (Table 5). [56][57][58][59][60][61][62][63][64][65][66][67][68][69] More recently, high effective rates (68% and 80%) of a combination chemotherapy with paclitaxel, ifosfamide and cisplatin (TIP) in the treatment of refractory disease were reported by Beyer et al and Motzer et al 60,61 The results reported by Motzer et al showed a high response rate to the TIP regimen in patients with relapsed testicular cancer after conventional dose first-line chemotherapy. 61 Motzer and associates also reported the result of dose-intensive salvage therapy with paclitaxel, ifosfamide, carboplatin and etoposide (PICP) for cisplatin-resistant germ cell tumor patients with unfavorable prognostic features, achieving a 57% CR rate.…”
Section: Poor-prognosis Diseasementioning
confidence: 99%